ANALISIS TENTANG DEKEMALISASI DI TURKI PASCA ATATURK - Zainal, Nur Aliyah (Jurnal Politik Profetik, 2017)
The failure of the coup attempt in Turkey this year showed the support for Kemalism proved with only a small group of military who do. Kemalism that carries nationalism, secularism and Westernism have lived for many years in Turkey. But into the early 2000s with the victory of the AK Party and the election of Erdogan’s Islamist assessed in several key positions such as mayor and then Prime Minister and now President showed the phenomenon of decline in support for Kemalism and the Turkish people’s desire to return to practice religion freely. Not only that, the constitutional changes also contribute to it.